PATENTS IN GENOMICS AND HUMAN GENETICS - Cook-Deegan, Robert (2010)
Genomics and human genetics are scientifically fundamental and commercially valuable. These fields grew to prominence in an era of growth in government and nonprofit research funding, and of even greater growth of privately funded research and development in biotechnology and pharmaceuticals. Patents on DNA technologies are a central feature of this story, illustrating how patent law adapts---and sometimes fails to adapt---to emerging genomic technologies. In instrumentation and for therapeutic proteins, patents have largely played their traditional role of inducing investment in engineering and product development, including expensive postdiscovery clinical research to prove safety and efficacy. Patents on methods and DNA sequences relevant to clinical genetic testing show less evidence of benefits and more evidence of problems and impediments, largely attributable to university exclusive licensing practices. Whole-genome sequencing will confront uncertainty about infringing granted patents but jurisprudence trends away from upholding the broadest and potentially most troublesome patent claims.